Development of paper-based microfluidic analytical device (μPAD) for the determination of paracetamol in water samples: Optimization using response surface methodology (RSM) - Nejat Mohammednur; Ahmed Hussen; Feleke Zewge (Applied Water Science)
Abstract Detecting and quantifying pharmaceutical compounds in various environmental matrices is complex and challenging. This difficulty stems from the trace levels at which these compounds are found and the lack of analytical methods that are rapid, cost-effective, and portable. To address these challenges, this study aimed to develop microfluidic paper-based analytical devices (μ-PADs) using beeswax screen printing for fabrication. Key parameters, including reaction time, concentration, reagent volume, and channel length, were optimized using response surface methodology. Under optimal conditions of 5 ppm sample concentration, 10 μL reagent volume, 10 min reaction time, and 2 cm channel length, the analytical performance of the μPAD was evaluated and compared with the standard UV–Vis spectrophotometry method. The microfluidic analytical device demonstrated detection limits at 0.03 μg/ml, compared to 0.01 μg/ml for the UV–Vis spectrophotometer. Although the sensitivity of µ-PADs in this study (0.03 μg/ml) is lower than that of UV–Vis (0.01 μg/ml), it represents an improvement over the previous µ-PAD report (1 μg/ml) on the same analytes. Both methods exhibited commendable precision, with a relative standard deviation below 2%. Additionally, recovery rates were acceptable and comparable, ranging from 86.8 to 99.6% for µ-PADs and 96.5–99% for UV–Vis. The analytical performance evaluation suggests that µPADs provide excellent sensitivity, precision, and accuracy for trace-level paracetamol analysis. A paired t-test further confirmed no statistically significant difference between the two methods, underscoring the promising potential of µ-PADs for trace-level paracetamol quantification in water samples without conventional analytical instruments.